Brand Perceptions and Preferences of Malaysians: An Exploratory Study of Malays, Chinese and the Indians. - Juzar, Rumana (2009)
The world today is becoming more homogenized and multicultural societies are emerging. The increased diversity in the local marketplaces of some nations brings much focus to be researched on. Microcultures and national cultures are important dimensions for marketers to predict consumer behaviour. In this study, the concepts of ethnicity and acculturation in Malaysia is examined to predict if there are similarities or differences among the three ethnic groups: Malays, Chinese and the Indians. This is to explore if the effects of ethnicity and acculturation play a part on their brand consumption habits. The brand perceptions and preferences of the three groups were investigated through semi-structured personal interviews and focus groups. The findings suggest that global brands were preferred compared to local brands, on the cues of price, quality, user and usage imagery, country-of-origin effects and others. Therefore, there were no differences found between the three groups in terms of their brand preference and purchasing attitudes. Their ethnic identity did not dictate their perceptions of brands but in terms of food consumption, it played a part. Acculturation into the Malaysian culture was noted in their dietary habits. Religion also was an emergent theme.